A review of the palynostratigraphy of Gondwana sediments from the Godavari Graben, India: Global comparison and correlation of the Permian-Triassic palynoflora. (1st September 2018) - Jha, Neerja; Aggarwal, Neha; Mishra, Shreya
Graphical abstract: Highlights: Permian-Triassic palynostratigraphy of Chintalapudi sub basin deduced. Documented the existence of two coal bearing horizons. Late Permian-early Triassic palynoflora resembles with Salt Range and Antarcatica. Study strengthen the existence of Guttulapollenites phytogeographic province. Abstract: The continental sequences of Gondwana deposits from the Chintalapudi sub-basin of the Godavari Graben, South India have been palynologically investigated to explore the Permian–Triassic palynoflora. Total 11 distinct palynoassemblages belonging to the Asselian-Sakmarian (I, II), Artinskian (III, IV), Guadalupian (V, VI), Lopingian (VII, VIII, IX), Induan (X) and Olenekian (XI) age have been documented. The palynological studies support the existence of the two coal-bearing horizons in the Chintalapudi sub-basin, one in the Karharbari and Barakar formations (Sakmarian-Artinskian) while other in the Raniganj Formation (Guadalupian-Lopingian). The lack of the Upper Barakar and Barren Measures (Roadian) palynoflora indicates apparent discordance in stratigraphic sequence in this sub-basin. Presently studied the Permian-Triassic palynofloral transition has been found akin to the palynoflora of the Salt Range, Madagascar, Antarctica, Australia and South Africa. The palynofloral correlation supports the presence of Guttulapollenites palaeophytogeographic province in the Gondwana during the Guadalupian– Lopingian. The Guttulapollenites palaeophytogeographic province co-exists with the Glossopteris megafloral province and extends from the Salt Range in the north to Amery Basin in the south, Mid Zambesi-Luangwa Basin in the west to Satpura-Wardha-Godavari Basin in the east.